Identification of significant design factors for diesel spray combustion control through comprehensive experiments with various multi-hole nozzle internal geometries. (February 2022) - Watanabe, Naoki; Kurimoto, Naoki; Serizawa, Kazufumi; Yoshino, Mutsumi; Skeen, Scott; Pickett, Lyle M
It is well known that nozzle internal geometries affect the characteristics of diesel spray and combustion. However, despite a number of studies, the effects are difficult to generalize. It is also not clear which spray features are more important for combustion than others. To investigate these subjects, a comprehensive dataset on diesel spray combustion was obtained with 20 variations of multi-hole injector nozzle. The 20 variations had different combinations of orifice diameter, orifice length, sac length and orifice hub-to-tip ratio, which cover the large range of existing production injectors. Vapor penetration, vapor width, ignition delay time, ignition distance and lift-off length were quantified using schlieren and excited-state hydroxyl radical (OH*) chemiluminescence imaging for an isolated plume emerging from these different nozzles. The experiments were conducted with Japanese diesel fuel in a constant-volume diesel spray combustion facility at Sandia National Laboratories. The results were analyzed with response surface and Lasso regression analysis to identify significant design factors for spray combustion. Orifice diameter has large effects on spray combustion. Orifice length, sac length, orifice hub-to-tip ratio and their interactions have effects on spray combustion, but each effect is smaller than the effect of orifice diameter. Vapor penetration is a significant design factor for ignition delay time, ignition distance and lift-off length, while vapor width is not. Lift-off length is well-explained by ignition distance and ignition delay time. Ignition distance should be taken into consideration as a significant design factor for lift-off length as well as ignition delay time.